I got the answer 18.79
I believe this is correct, Please tell me if im wrong. :)
Answer:
The volume of the pill is ![V=452\ mm^{3}](https://tex.z-dn.net/?f=V%3D452%5C%20mm%5E%7B3%7D)
Step-by-step explanation:
Find the volume of the pill in cubic millimeters
we know that
The volume of the pill is equal to the volume of the cylinder plus the volume of a sphere (two hemisphere is equal to one sphere)
so
we have
![V=\frac{4}{3}\pi r^{3}+\pi r^{2}h](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B4%7D%7B3%7D%5Cpi%20r%5E%7B3%7D%2B%5Cpi%20r%5E%7B2%7Dh)
![r= (18-12)/2=3\ mm\\ h=12\ mm](https://tex.z-dn.net/?f=r%3D%20%2818-12%29%2F2%3D3%5C%20mm%5C%5C%20h%3D12%5C%20mm)
assume
![\pi =3.14](https://tex.z-dn.net/?f=%5Cpi%20%3D3.14)
substitute
![V=\frac{4}{3}(3.14)(3)^{3}+(3.14)(3)^{2}(12)\\V=452\ mm^{3}](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B4%7D%7B3%7D%283.14%29%283%29%5E%7B3%7D%2B%283.14%29%283%29%5E%7B2%7D%2812%29%5C%5CV%3D452%5C%20mm%5E%7B3%7D)
<em>Note: Your answer choices remain a little unclear. But, I have solved the concept and solution, so you can easily figure it out.</em>
Answer:
![\left(-7x^0+5x^2-x+6\right)-\left(-8x^2+x+3\right)=13x^2-2x-4](https://tex.z-dn.net/?f=%5Cleft%28-7x%5E0%2B5x%5E2-x%2B6%5Cright%29-%5Cleft%28-8x%5E2%2Bx%2B3%5Cright%29%3D13x%5E2-2x-4)
Step-by-step explanation:
Given the expression
![\left(-7x^0+5x^2-x+6\right)-\left(-8x^2+x+3\right)](https://tex.z-dn.net/?f=%5Cleft%28-7x%5E0%2B5x%5E2-x%2B6%5Cright%29-%5Cleft%28-8x%5E2%2Bx%2B3%5Cright%29)
solving the expression
![=-7x^0+5x^2-x+6-\left(-8x^2+x+3\right)](https://tex.z-dn.net/?f=%3D-7x%5E0%2B5x%5E2-x%2B6-%5Cleft%28-8x%5E2%2Bx%2B3%5Cright%29)
apply the rule: ![a^0=1,\:a\ne \:0](https://tex.z-dn.net/?f=a%5E0%3D1%2C%5C%3Aa%5Cne%20%5C%3A0)
![=-7+5x^2-x+6-\left(-8x^2+x+3\right)](https://tex.z-dn.net/?f=%3D-7%2B5x%5E2-x%2B6-%5Cleft%28-8x%5E2%2Bx%2B3%5Cright%29)
![=-7+5x^2-x+6+8x^2-x-3](https://tex.z-dn.net/?f=%3D-7%2B5x%5E2-x%2B6%2B8x%5E2-x-3)
simplify
![=13x^2-2x-4](https://tex.z-dn.net/?f=%3D13x%5E2-2x-4)
Therefore, the simplified form is:
![\left(-7x^0+5x^2-x+6\right)-\left(-8x^2+x+3\right)=13x^2-2x-4](https://tex.z-dn.net/?f=%5Cleft%28-7x%5E0%2B5x%5E2-x%2B6%5Cright%29-%5Cleft%28-8x%5E2%2Bx%2B3%5Cright%29%3D13x%5E2-2x-4)
<em>Note: Your answer choices remain a little unclear. But, I have solved the concept and solution, so you can easily figure it out.</em>